Playback‐Aided Surveys and Acoustic Monitoring in the Detection of the Endangered Forest Owlet Athene blewitti - Amrutha Rajan; Aditi Neema; Pranav G. Trivedi; Sejal Worah; Meera M. R.; Shomita Mukherjee; V. V. Robin (Ecology and Evolution)
ABSTRACT Monitoring rare and endangered species over the long term is challenging due to limited historical data and comparable methods. Climate and landscape changes can significantly impact species distributions, driving some to extinction. The Forest Owlet is an endangered bird considered extinct but rediscovered after 113 years in 1997. Since its rediscovery, followed by the description of its calls, there have been regular recent sightings of the species from newer locations, leading to its downlisting in the IUCN Red List from critically endangered to endangered. In the Dang region in Gujarat, India, there have been no historical records despite previous systematic ornithological studies over three decades, but have multiple sightings over the last few years. Although we now know a little more about the broad association of the species occurrence with habitat and climate variables, a major focus of this study is to estimate the reasons for the “appearance” of the Forest Owlet in Dangs. We revisited locations of past surveys to determine if the species is currently found in the study sites where it was previously unrecorded. We also examine whether new survey methods using playback of its call could enhance its detection. During resurveys, we located the Forest Owlet at new, previously unrecorded locations. Analyses of satellite imagery products revealed significant changes in the broader Dang landscape, including the loss of native forests, increased agriculture, and shifts in mean maximum temperature and rainfall. Our research suggests playback can enhance detection, although its effectiveness varies across landscapes. A detection strategy for long‐term monitoring was developed using different acoustic detectors. An effective detection distance of 300 m within the habitat was achieved using automated recording units (ARUs). Although the species responds to climate and habitat change, the cause of the increased reports of this endangered species remains undetermined. However, we found increased detections using newer survey techniques involving bioacoustics. We recommend using these techniques carefully for future baseline studies, which are urgently required.